CORRELATION BETWEEN SLEEP QUALITY AND BODY MASS INDEX IN ADOLESCENTS IN DENPASAR - Zaffyr, Darryl Rex; Sundari, Luh Putu Ratna; Primayanti, I Dewa Ayu Inten Dwi; Adiatmika, I Putu Gede (Sport and Fitness Journal; Vol 9 No 3 (2021): Volume 9, No. 3, September 2021DO - 10.24843/spj.2021.v09.i03.p05, 2021)
Introduction: Obesity is a pathological condition under which extra fat is accumulated from the body's required needs. Complications such as hypertension, dyslipidemia, diabetes, fatty liver disease and psychosocial problems can occur in a person who is overweight and obese in adolescence. Sleep quality represents satisfaction with the sleep experience by integrating sleep initiation aspect, managing sleep time, meeting sleep needs, and feeling refreshed when waking up. One of the factors that can lead to overweight and obesity is poor sleep quality. This research attempts to establish the association between sleep quality and body mass index in adolescents in Denpasar. Methods : This research was a cross-sectional analytical study using the Pittsburgh Sleep Quality Index questionnaire to determine the quality of sleep and measurement of the body mass index of 280 high school students in Denpasar. Results : Somers’D correlation test results showed no relationship (p = 0.108) between sleep quality and body mass index in adolescents. Conclusions : There is no correlation between sleep quality and body mass index in adolescents in Denpasar. Further studies are needed related to other factors that affect an adolescent's body mass index.